Interorganizational performance evaluation: metrics for interorganizational cost management - Pedersini, Daiana Rafaela; Castanha, Eduardo Tramontin; Gasparetto, Valdirene; Ensslin, Sandra Rolim (Revista de Administração da UFSM, 2025)
Purpose: Faced with the lack of a comprehensive model that assesses the multidimensionality of IOCM and its underlying aspects, the objective of this research was to propose a set of metrics to assess relational performance during Interorganizational Cost Management efforts. Methodology: A literature review was carried out, based on the procedures suggested by ProKnow-C, consisting of two sets of articles (i) performance evaluation and (ii) interorganizational cost management, of which a content analysis was carried out to propose a set of metrics. Results: From the theoretical assumptions and empirical findings evidenced by the relevant literature, the metrics were constructed considering as measurement objects open book accounting, purpose of information, interorganizational cooperation, management information systems and IOCM. In addition, characteristics that represent interorganizational performance evaluation systems were identified. It was identified that the evaluation of performance in the management of interorganizational costs constitutes a theme in development that covers several research possibilities. OriginalityContributions: In the emerging organizational context, in which organizations have sought to establish collaborative alliances, interorganizational performance assessment is evolving to meet new organizational configurations. At the same time, interorganizational relationships have triggered joint efforts to promote interorganizational cost management. The study summarizes characteristics of extended systems and essential elements for the functioning of IOCM and translates these characteristics into metrics capable of evaluating the performance of interorganizational relationships.